The heart of Spain. Anthology of fiction, nonfiction and poetry. Ed. by A. Bessie. [With an introd by D. Parker. With contribs of L. MacNeice, Domino, F. Garcia Lorca a.o.] (Veterans of the Abraham Lincoln Brigade, 1952)
With bibliogr.